An Anthropolinguistic Analysis of Cultural Values and Social Structure in the Traditional Songs Kampuang Nan Jauah di Mato and Furusato - Lestari, Imelda Indah; Putri, Darni Enzimar; Rumbardi, Rumbardi (Andalas International Journal of Socio-Humanities, 2025)
This study examines the cultural values, worldview, and social structure embedded in the lyrics of two traditional songs: the Minangkabau song "Kampuang Nan Jauah di Mato" and the Japanese song "Furusato." Drawing on anthropolinguistic theory (Duranti, Foley, and Kramsch) and Newmark's (1988) classification of cultural lexical items, the research analyzes how language functions as a symbolic representation of cultural identity, collective memory, and social relations. Using a comparative qualitative approach with the comparison-matching (CM) and comparison-differentiating (CD) techniques, the study identifies similarities and differences in ecological, social, and ideational cultural elements reflected in the song lyrics. The findings suggest that both songs convey a profound emotional connection to the homeland as a source of identity and memory. However, Kampuang Nan Jauah di Mato emphasizes Minangkabau values of collectivism, family solidarity, and communal cooperation rooted in matrilineal and migratory (merantau) traditions. In contrast, Furusato highlights Japanese cultural values such as harmony (wa), emotional sensitivity (mono no aware), and strong social bonds (kizuna) formed through family and childhood relationships within rural communities. Ecological imagery, including mountains, rivers, and village landscapes, functions as a shared symbolic resource that reflects each culture's relationship with nature. This study concludes that traditional songs serve as living cultural texts, preserving social memory and articulating culturally specific views of life through language.